The impact of company characteristics behavior on disclosure of corporate social responsibility - Imron, Moch. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Corporate Social Responsibility (CSR) is defined as corporate social responsibility, which is a matter of corporate environmental governance, and this environmental governance is an added value for multinational companies, including companies located in Indonesia. This study aims to determine the effect of size, profile, and institutional ownership on the disclosure of corporate social responsibility. GRI G4 is used for CSR disclosure. This research uses quantitative research methods. Purposive sampling was used for 150 companies listed on the Indonesia Stock Exchange in 2019–2022. Secondary data from www.idx.co.id and related company websites is used. Multiple regression analysis (OLS) was applied. The results of this study are hypothesis testing, which shows that company profile and institutional ownership structure substantially affect the disclosure of social responsibility, while company size does not.